Особливості хірургічного лікування диференційованого раку щитоподібної залози - Стернюк, Ю. М.; Огорчак, М. А.; Ніедерле, Б. (Clinical Endocrinology and Endocrine Surgery, 2011)
The optimal tactics of the radical surgical treatment of the differentiated thyroid cancer was proposed. It was based on the peculiarities of the regional lymphatic spread of the thyroid cancer according to which the thyroidectomy with en bloc central lymph nodes dissection is performed with diagnostic lymphadenectomy and dissection of other regions due to the metastatic involvement. The use of this surgical tactics improves the 5-year recurrence survival rate on 11.38% (p=0,004), and in the case of the papillary cancer on 11.22% (p=0,011).